ANXIETY LEVELS AND PERCUTANEOUS CARDIAC INTERVENTION (PCI) IN STEMI AND NSTEMI PATIENTS AT BANGIL HOSPITAL - MERBAWANI, RARAS (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
According to the World Health Organization, coronary heart disease, including STEMI and NSTEMI, is the leading cause of noncommunicable disease-related mortality worldwide. First treatment for STEMI-NSTEMI patients was reperfusion with Percutaneous Coronary Intervention (PCI). Anxiety increases the difficulty of controlling cardiac disease in patients with a diagnosis of STEMI and NSTEMI who will undergo PCI surgery. This study employs a cross-sectional correlation analysis methodology. Patients with coronary heart disease diagnosed with STEMI and NSTEMI who are receiving treatment at Bangil Hospital constituted the population. Forty respondents were selected using a technique called purposive sampling. Percutaneous Coronary Intervention (PCI) is the independent variable. While apprehension levels are the dependent variable. At a Sig (2-tailed) value of 0.05, Ho was rejected and H1 was accepted, indicating that there was a correlation between preparation for surgery (Giving Informed Consent) Percutaneous Coronary Intervention and anxiety levels in STEMI - NSTEMI patients at Bangil Hospital. Consent was obtained prior to the decision to perform PCI. If the patient agrees to informed consent, the procedure will continue; if the patient refuses, the procedure will not be performed. The conclusion of this study is that Percutaneous Coronary Intervention (PCI) procedures are associated with a lower level of anxiety the better the preparation for surgery (providing informed consent) is.